A Certain Studies on Mathematical Modeling: An Optimization Oriented the Replacement of Items whose Efficiency Deteriorates with Time - Sahani, Suresh Kumar; Mandal, Deb Narayan; Sahani, Kameshwar (Darul Yasin Al Sys, 2024)
According to the definitions of operation research, it may be regarded as a methodology, an approach, a set of techniques, a team activity, a mixing of various disciplines, an extension of a particular discipline, a new discipline, a vocation, even a religion. There are many problems in today's world that involve the replacement of items, and in this paper we solve a few of these problems and also discuss the day-to-day replacement of items with maintenance costs that increase over time as well as their value as time goes on.